Penerapan Algoritma Prim dalam Menentukan Rute Prioritas Pengiriman Paket Express - Arya Bima Mohammad Heriansyah; Rinaldi Rizwar; Muhamad Rafliansyah; Efrans Christian; Viktor Handrianus Pranatawijaya (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
This research analyzes the use of the Prim Algorithm in determining priority routes for package delivery by express service couriers. Through case studies, this research evaluates the efficiency of package delivery by considering delivery priority and the distance the courier will travel. The research results show that the Prim Algorithm is effective in minimizing delivery loads by connecting priority delivery points with minimal travel distance. This research method uses the Prim Algorithm to create a delivery route graph that connects all priority delivery points with a minimum travel distance, with data including the location of the delivery point, priority and distance between locations. The results show that the Prim Algorithm is effective in minimizing delivery load by generating optimal routes, allowing couriers to prioritize package delivery efficiently. This proves the important role of the Prim Algorithm in package delivery strategies for express service couriers.